Nitroxide mediated degradation of anthocyanidins - Butković, Vjera (Array, 2009)
Summary: The degradation of the six anthocyanidins (pelargonidin, cyanidin, delphinidin, peonidin, petunidin and malvidin) mediated by the nitroxides: 2,2,6,6-tetramethylpiperidine-1-oxyl (Tempo), 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (Tempol) and 4-methoxy-2,2,6,6-tetramethylpiperidine1-oxyl (4-CH3O-Tempo) at 25 °C in aqueous acid solution was investigated spectrophotometrically and by EPR and HPLC measurements. The reaction kinetics were followed under pseudo-first order conditions using a large excess of nitroxide reactants. The spontaneous degradation of anthocyanidins under these conditions is several orders of magnitude slower, and it did not influence the measurements. However, it was found that the reaction rate increases with the age of acidified nitroxide solutions, reaching a maximum after 24 hours. This result indicates that in every case the oxoammonium cation, generated by disproportionation of nitroxyl radicals, is somewhat more reactive toward anthocyanidins than the nitroxyl itself. The products were identified by HPLC as ring substituted benzoic acids. The relative reactivities of the six anthocyanidins and the accelerating influence of the p-substituent of nitroxides on the reaction is discussed